The role of the irritative zone and of the number and distribution of calcifications in the severity of epilepsy associated with intracranial calcifications Papel da zona irritativa e do número e distribuição das calcificações na gravidade da epilepsia associada com calcificações intracerebrais - Pedro André Kowacs; Enio Rogacheski; Juliano Muzzio; Lineu César Werneck (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To determine the influence of the location of the irritative zone, and the number and the distribution of the intracranial calcifications in the severity of epilepsy associated with intracranial calcifications. METHOD: We studied 47 patients with epilepsy and intracranial calcifications, 24 with normal (Group A) and 23 with abnormal interictal EEGs (Group B), a control group (n=21) with abnormal interictal EEGs and normal CT-scans (Group C). Clinical, electroencephalographic and neuroradiological features were compared among groups. RESULTS: Temporal lobe interictal EEG abnormalities were found in 23/24 Group B patients, and in all Group C patients. Most Group B and Group C patients presented temporal lobe seizure symptomatology, whereas in most Group A patients symptomatology was rolandic (p=0.0001). Epilepsy was more severe in Group B and Group C patients than in Group A patients (p=0.0001 and p=0.0054). No relationship was found between the number of calcifications and epilepsy severity. CONCLUSION: An irritative zone at the temporal lobe is more relevant in determining the severity, symptomatology and frequency of seizures than the number and location of calcifications. OBJETIVO: Testar a relevância do lobo temporal na epilepsia associada a neurocisticercose inativa. MÉTODO: Foram selecionados 47 pacientes com epilepsia e calcificações intracerebrais, 22 com EEGs intercríticos normais (Grupo A) e anormais em 23 (Grupo B) e um grupo controle (n=21) com EEGs intercríticos anormais sem calcificações intracerebrais (Grupo C). Características clínicas, eletrencefalográficas e neuroradiológicas foram comparadas entre os grupos. RESULTADOS: Encontramos anormalidades eletrencefalográficas temporais em 23/24 dos pacientes do Grupo B e em todos do Grupo C. Na maioria dos pacientes do Grupo B e Grupo C a sintomatologia ictal foi interpretada como temporal, porém no Grupo A como rolândica (p=0,0001) A epilepsia foi mais grave nos grupos Grupo B e Grupo C que no Grupo A (p=0,0001 e 0,0054). Não houve relação direta entre o número de calcificações e a gravidade da epilepsia. CONCLUSÃO: Uma zona irritativa sobre o lobo temporal é mais relevante na gravidade, sintomas e freqüência das crises que o número e a localização das calcificações.